Bictegravir/emtricitabine/tenofovir alafenamide in older individuals with HIV: Results of a 96‐week, phase 3b, open‐label, switch trial in virologically suppressed people ≥65 years of age. Issue 1 (8th May 2022) - Maggiolo, Franco; Rizzardini, Giuliano; Molina, Jean‐Michel; Pulido, Federico; De Wit, Stephane; Vandekerckhove, Linos; Berenguer, Juan; D'Antoni, Michelle L.; Blair, Christiana; Chuck, Susan K.; Piontkowsky, David; Martin, Hal; et al.
Abstract: Objectives: Bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) is an effective treatment for HIV‐1 infection; however, clinical trial data in older people living with HIV (PLWH) are lacking. The primary 24‐week and secondary 48‐week analyses of study GS‐US‐380‐4449 (NCT03405935), which assessed the efficacy and safety of switching to B/F/TAF in older PLWH, have been published. Here we report the results of the final 96‐week analyses from the study. Methods: In this 96‐week, phase 3b, open‐label, single‐arm trial, virologically suppressed PLWH aged ≥65 years switched from elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide or a tenofovir disoproxil fumarate‐based regimen to B/F/TAF. Viral suppression, resistance, immune response, safety, tolerability and adherence were evaluated through week 96. Results: Of 90 participants screened, 86 were enrolled and switched to B/F/TAF. No participants had HIV‐1 RNA ≥50 copies/ml (by FDA Snapshot algorithm) at weeks 72 or 96; virologic suppression rates were 94.2% (81/86; 95% CI 87.0–98.1) and 74.4% (64/86; 95% CI 63.9–83.2), respectively. No treatment‐emergent resistance was observed, and CD4 counts remained stable. There were no study drug‐related serious adverse events. Three participants experienced drug‐related treatment‐emergent adverse events that led to premature drug discontinuation. There were no clinically relevant changes from baseline to week 96 in fasting lipid parameters, and the median change in body weight at week 96 was 0.0 kg (IQR −2.3, 2.0). Median self‐reported adherence was 100% (IQR 100–100%). Conclusions: Switching to B/F/TAF is an effective long‐term option for virologically suppressed adults ≥65 years of age, with favourable safety and tolerability profiles in this population.